Pulmonary Neuroendocrine Cells Secrete γ-Aminobutyric Acid to Induce Goblet Cell Hyperplasia in Primate Models - Barrios, Juliana; Kho, Alvin T.; Aven, Linh; Mitchel, Jennifer A.; Park, Jin-Ah; Randell, Scott H.; Miller, Lisa A.; Tantisira, Kelan G.; Ai, Xingbin (American journal of respiratory cell and molecular biology, 2019)
Mucus overproduction is a major contributor to morbidity and mortality in asthma. Mucus overproduction is induced by orchestrated actions of multiple factors that include inflammatory cytokines and γ-aminobutyric acid (GABA). GABA is produced only by pulmonary neuroendocrine cells (PNECs) in the mouse lung. Recent studies in a neonatal mouse model of allergic inflammation have shown that PNECs play an essential role in mucus overproduction by GABA hypersecretion. Whether PNECs mediate dysregulated GABA signaling for mucus overproduction in asthma is unknown. In this study, we characterized the cellular source of GABA in the lungs of nonhuman primates and humans and assessed GABA secretion and signaling in primate disease models. We found that like in mice, PNECs were the major source of GABA in primate lungs. In addition, an infant nonhuman primate model of asthma exhibited an increase in GABA secretion. Furthermore, subjects with asthma had elevated levels of expression of a subset of GABA type α (GABAα) and type β (GABAβ) receptors in airway epithelium compared with those of healthy control subjects. Last, employing a normal human bronchial epithelial cell model of preinduced mucus overproduction, we showed pharmaceutical blockade of GABAα and GABAβ receptor signaling reversed the effect of IL-13 on gene expression and goblet cell proliferation. Together, our data demonstrate an evolutionarily conserved intraepithelial GABA signaling that, in concert with IL-13, plays an essential role in mucus overproduction. Our findings may offer new strategies to ameliorate mucus overproduction in patients with asthma by targeting PNEC secretion and GABA signaling.